Real time PCR to detect the environmental faecal contamination by Echinococcus multilocularis from red fox stools. - Knapp, Jenny; Millon, Laurence; Mouzon, Lorane; Umhang, Gérald; Raoul, Francis; Ali, Zeinaba Said; Combes, Benoît; Comte, Sébastien; Gbaguidi-Haore, Houssein; Grenouillet, Frédéric; Giraudoux, Patrick (Veterinary Parasitology, 2014)
International audience : The oncosphere stage of Echinococcus multilocularis in red fox stools can lead, after ingestion, to the development of alveolar echinococcosis in the intermediate hosts, commonly small mammals and occasionally humans. Monitoring animal infection and environmental contamination is a key issue in public health surveillance. We developed a quantitative real-time PCR technique (qPCR) to detect and quantify E. multilocularis DNA released in fox faeces. A qPCR technique using a hydrolysis probe targeting part of the mitochondrial gene rrnL was assessed on (i) a reference collection of stools from 57 necropsied foxes simultaneously investigated using the segmental sedimentation and counting technique (SSCT) (29 positive for E. multilocularis worms and 28 negative animals for the parasite); (ii) a collection of 114 fox stools sampled in the field: two sets of 50 samples from contrasted endemic regions in France and 14 from an E. multilocularis-free area (Greenland). Of the negative SSCT controls, 26/28 were qPCR-negative and two were weakly positive. Of the positive SSCT foxes, 25/29 samples were found to be positive by qPCR. Of the field samples, qPCR was positive in 21/50 (42%) and 5/48 (10.4%) stools (2 samples inhibited), originating respectively from high and low endemic areas. In faeces, averages of 0.1pg/μl of DNA in the Jura area and 0.7pg/μl in the Saône-et-Loire area were detected. All qPCR-positive samples were confirmed by sequencing. The qPCR technique developed here allowed us to quantify environmental E. multilocularis contamination by fox faeces by studying the infectious agent directly. No previous study had performed this test in a one-step reaction.